Comparative Functional Genomics and the Bovine Macrophage Response to Strains of the Mycobacterium Genus - Rue-Albrecht, KÃ©vin; Magee, David A.; Killick, Kate E.; Nalpas, Nicolas C.; Gordon, Stephen V.; MacHugh, David E. (Frontiers in immunology, 2014)
Mycobacterial infections are major causes of morbidity and mortality in cattle and are also potential zoonotic agents with implications for human health. Despite the implementation of comprehensive animal surveillance programs, many mycobacterial diseases have remained recalcitrant to eradication in several industrialized countries. Two major mycobacterial pathogens of cattle are Mycobacterium bovis and Mycobacterium avium subspecies paratuberculosis (MAP), the causative agents of bovine tuberculosis (BTB) and Johne's disease (JD), respectively. BTB is a chronic, granulomatous disease of the respiratory tract that is spread via aerosol transmission, while JD is a chronic granulomatous disease of the intestines that is transmitted via the fecal-oral route. Although these diseases exhibit differential tissue tropism and distinct complex etiologies, both M. bovis and MAP infect, reside, and replicate in host macrophages - the key host innate immune cell that encounters mycobacterial pathogens after initial exposure and mediates the subsequent immune response. The persistence of M. bovis and MAP in macrophages relies on a diverse series of immunomodulatory mechanisms, including the inhibition of phagosome maturation and apoptosis, generation of cytokine-induced necrosis enabling dissemination of infection through the host, local pathology, and ultimately shedding of the pathogen. Here, we review the bovine macrophage response to infection with M. bovis and MAP. In particular, we describe how recent advances in functional genomics are shedding light on the host macrophage-pathogen interactions that underlie different mycobacterial diseases. To illustrate this, we present new analyses of previously published bovine macrophage transcriptomics data following in vitro infection with virulent M. bovis, the attenuated vaccine strain M. bovis BCG, and MAP, and discuss our findings with respect to the differing etiologies of BTB and JD.